The Affect of TQM Dimensions on Company Performance Improvement - Jestawana, Ainur Salwa; Waluyowati, Nur Prima (Jurnal Management Risiko dan Keuangan, 2025)
This quantitative study aims to analyze the influence of customer focus, teamwork, continuous improvement, training and education, and employee empowerment on the performance of CV Kirana Bahari Indonesia. These five variables represent the core principles of Total Quality Management (TQM), which are believed to enhance quality and organizational competitiveness. The data were collected through questionnaires distributed to 82 respondents who are permanent employees of the company and analyzed using multiple linear regression with SPSS. The study finds that all five TQM variables simultaneously have a significant effect on company performance. However, only customer focus and employee empowerment show a significant partial effect, while teamwork, continuous improvement, and training and education do not have a significant impact. These findings indicate that the implementation of TQM at CV Kirana Bahari Indonesia has not been evenly or optimally executed across all aspects. There remains a gap between employee perceptions and the actual impact on performance improvement. This study contributes theoretically by emphasizing that the effectiveness of TQM depends greatly on organizational context, the quality of implementation, and the active involvement of all company elements.